2007
DOI: 10.1175/jcli4000.1
|View full text |Cite
|
Sign up to set email alerts
|

Fall Persistence Barrier of Sea Surface Temperature in the South China Sea Associated with ENSO*

Abstract: The authors investigate persistence characteristics of sea surface temperature (SST) in the South China Sea (SCS) in association with El Niño-Southern Oscillation (ENSO). It is found that a persistence barrier exists around October and November. This fall persistence barrier (FPB) is well recognized in the developing phase of strong ENSO cases, but becomes vague in weak ENSO and normal (non-ENSO) cases. During a strong El Niño developing year, salient features of the SCS SST anomaly (SSTA) associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 44 publications
(71 reference statements)
4
54
3
Order By: Relevance
“…It is found that the appearance of the lower-level Philippine Sea circulation anomaly is closely related to evident spring rainfall variability in Taiwan. This circulation anomaly was found to move eastward across the IO into the South China Sea during fall and anchor in the Philippine Sea during winter (Chen et al 2007). Such developing processes allow us to detect the occurrence of the Philippine Sea circulation anomaly at least one to two seasons prior to spring.…”
Section: Discussionmentioning
confidence: 90%
“…It is found that the appearance of the lower-level Philippine Sea circulation anomaly is closely related to evident spring rainfall variability in Taiwan. This circulation anomaly was found to move eastward across the IO into the South China Sea during fall and anchor in the Philippine Sea during winter (Chen et al 2007). Such developing processes allow us to detect the occurrence of the Philippine Sea circulation anomaly at least one to two seasons prior to spring.…”
Section: Discussionmentioning
confidence: 90%
“…However, the dynamic process is not clear, and more in-depth investigation is required in the future. Chen et al (2007) have already examined the relationship between the SCS FPB and ENSO, and they pointed out that the SCS FPB is well-recognized in the developing phase of strong ENSO cases, but becomes vague in weak ENSO and non-ENSO cases. We perform similar computations for the SCS and the Indonesia region.…”
Section: The Relationship Between the Persistence Barrier And The Intmentioning
confidence: 99%
“…Chen et al (2007) found a fall persistence barrier (FPB) of SSTA in the South China Sea (SCS), and the SCS FPB is well-recognized in the developing phase of strong ENSO cases, but becomes vague in weak ENSO and non-ENSO cases. The SCS is located in the wellknown East Asian monsoon region, and variability of the ocean-atmosphere in the SCS region can have a noticeable impact on the East Asian climate (e. g., Huang and Sun, 1992;Shen and Lau, 1995;Tomita and Yasunari, 1996;Ose et al, 1997;Wang and Fan, 1999;Wang et al, 2001;Bueh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations